The Handbook of contemporary semantic theory - Lappin, Shalom; Fox, Chris 1965- (Chichester, West Sussex John Wiley & Sons, 2015)
"The second edition of The Handbook of Contemporary Semantic Theory presents a comprehensive introduction to cutting-edge research in contemporary theoretical and computational semantics. Features completely new content from the first edition of The Handbook of Contemporary Semantic Theory. Features contributions by leading semanticists, who introduce core areas of contemporary semantic research, while discussing current research. Suitable for graduate students for courses in semantic theory and for advanced researchers as an introduction to current theoretical work" -- Amazon.
Generalized quantifiers in natural language semantics / Dag Westerstêahl -- Scope / Chris Barker -- Plurals / Yoad Winter and Remko Scha -- Ellipsis / Ruth Kempson, Ronnie Cann, Arash Eshghi, Eleni Gregoromichelaki, and Matthew Purver -- Adjectival modification and gradation / Daniel Lassiter -- Presupposition and implicature / Christopher Potts -- The semantics of tense and aspect : a finite-state perspective / Tim Fernando -- Conditionals and modality / Magdalena Kaufmann and Stefan Kaufmann -- Semantics of questions / Andrzej Wiâsniewski -- The semantics of imperatives / Chris Fox -- Constructive type theory / Aarne Ranta -- Type theory with records for natural language semantics / Robin Cooper and Jonathan Ginzburg -- Curry typing, polymorphism, and fine-grained intensionality / Shalom Lappin -- Semantic complexity in natural language / Ian Pratt-Hartmann -- Implementing semantic theories / Jan van Eijck -- Vector space models of lexical meaning / Stephen Clark -- Recognizing textual entailment / Mark Sammons -- Natural logic / Lawrence S. Moss -- The syntax-semantics interface : semantic roles and syntactic arguments / Malka Rappaport Hovav and Beth Levin -- Reference in discourse / Andrew Kehler -- Probabilistic semantics and pragmatics : uncertainty in language and thought / Noah D. Goodman and Daniel Lassiter -- Semantics and dialogue / David Schlangen -- Semantics and language acquisition / Eve V. Clark.
Includes bibliographical references and indexes.
Keywords: Semantics -- Handbooks, manuals, etc; Semantics (Philosophy) -- Handbooks, manuals, etc